To further incorporate computer-aided designs to improve preoperative planning in total hip arthroplasty: a cohort study - Cheng, Kai; Zhu, Haotian; Peng, Yuanhao; Yan, Han; Wen, Xinghua; Cheng, Zixuan; Ding, Huanwen (Frontiers in Surgery, 2024)
Background Hip replacement surgeries are increasing in demand, requiring rigorous improvements to a mature surgical protocol. Postoperative patient dissatisfaction mainly stems from postoperative complications resulting from the inappropriate selection of prostheses to meet the needs of each patient. This results in prosthesis loosening, hospital-related fractures, and postoperative complex pain, which can all be attributed to inappropriate sizing. In this study, we aimed to further explore the intraoperative and postoperative benefits of incorporating computer-aided design (CAD) in preoperative planning for total hip arthroplasty (THA). Methods A total of 62 patients requiring total hip replacement surgery from January 2021 to December 2021 were collected and randomly divided into a preoperative computer-aided simulated group and a conventional x-ray interpretation group. The accuracy of implant size selection (femoral and acetabular implant) between the preoperative planning and surgical procedure of the two groups was compared. Patient parameters, perioperative Harris hip scores, operative time (skin-to-skin time), surgical blood loss, and postoperative hospital stay were recorded, and the differences between the two groups were statistically compared using a single sample t-test. Results All patients in the study were successfully operated on and achieved good postoperative functional recovery. With CAD, the selection of the most suitable-sized prosthesis was significantly more accurate compared to the control group (accuracy of the acetabular component between the CAD/control: 80.6%/61.3%, and accuracy of the femoral component: 83.9%/67.7%). Intraoperative blood loss (177.4/231.0 ml, P = 0.002), operation time (84.2 ± 19.8 min/100.3 ± 25.9 min, P = 0.008), duration of hospital stay (6.5 ± 3/9.1 ± 3.9 days, P = 0.003), and postoperative Harris hip score (81.9 ± 6.5/74.7 ± 11.1, P = 0.003) were compared to the control group and showed statistical significance. Conclusion Incorporating CAD into the preoperative planning of total hip arthroplasty can effectively guide the selection of the most suitable-sized prosthesis, reduce intraoperative blood loss, and promote short-term functional recovery after THA.